The Application of 30° Foot Elevation and Ankle Pump Techniques to Reduce Lower Limb Edema in Patients with Chronic Kidney Disease - Aeni Fitriyah; Siswoyo; Ika Adelia Susanti; Jumanto (Health and Technology Journal (HTechJ), 2026)
Lower extremity edema is a common complication in patients with stage 5 chronic kidney disease (CKD) due to fluid imbalance. Non-pharmacological therapies such as ankle pump exercises and 30°-foot elevation can be effective alternative interventions to reduce edema. This study aims to determine the effectiveness of combining ankle pump exercises and 30°-foot elevation in reducing the degree of edema in CKD patients. This research employed a quantitative descriptive case study method involving one patient with stage 5 CKD. The intervention consisted of ankle pump exercises and 30°-foot elevation conducted over three consecutive days. Each ankle pump session lasted 1 minute per position, and foot elevation was maintained for 5–10 minutes per session. Edema assessment was conducted pre- and post-intervention using the Grading Pitting Edema scale. The study showed no reduction in the edema grade from day one to day three. However, a decrease in edema depth was observed on the third day of the intervention, indicating that no significant reduction in the overall edema grade occurred. The application of ankle pump exercises and 30°-foot elevation over three days did not show a clinically significant reduction in edema. However, a positive effect began to emerge on the third day, with a 1 mm decrease in edema depth. The combination therapy has the potential to reduce lower extremity edema in CKD patients, but it requires consistent application and optimal intensity to achieve significant outcomes. This intervention may serve as a safe, non-invasive, and practical non-pharmacological option in evidence-based nursing care.